Performance Analysis Of Urban Transport Network In Denpasar City - I Gede Fery Surya Tapa; I Ketut Sutapa; Gede Teguh Prasetya Muttiwijaya; I Nyoman Indra Kumara; Decky Cipta Indrashwara (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2026)
Denpasar City has experienced many changes in the use of public transportation. In the previous year 18 active routes operating, while currently there are only 5 active routes. Therefore, an analysis of the performance of transportation, route network plans, and operational systems of the transportation is needed. Primary data was obtained from headway surveys, interview surveys, and on-board surveys. Vehicle Operating Cost (VOC) calculations, route network planning, and operational systems used the Department of Transportation method. The results of the analysis showed that almost all routes did not meet the standards of both operational performance and service quality. In this study, 6 routes were planned centered on the east parking lot of Renon field. The results of the new route planning are: Renon-Penatih with a route length of 18.7 km, a circulation time of 61.5 minutes and a total of 13 vehicles; Renon-Ubung with a route length of 22 km, a circulation time of 69.8 minutes and a total of 46 vehicles; Renon-Sanur with a route length of 14.3 km, a circulation time of 45.6 minutes and a total of 3 vehicles.